Mexican Medical Students Protest During COVID-19 Pandemic - Gabriela Torres-Hernández; Patricio García-Espinosa; Edgar Botello-Hernández; Diego Ortega-Moreno (University Library System, University of Pittsburgh, 2021)
During February  2021, a protest was organized by Mexican medical students through social media. About 200 interns, social service physicians and physicians protested peacefully in front of the city hall of Monterrey, Nuevo Leon, the capital of Mexico's second largest metropolitan area. Due to the current contingency situation, it was requested to attend with face shield and masks. The reason for the protest was to raise their voice due to the precarious situation where social service physicians are sent to rural areas of the country in which they have all the obligations of workers but without belonging to the working class - lacking the the benefits of this same as a living wage or fair working hours. The protesters were in limbo between student and worker. The protest also demanded justice for the sensitive death of young doctors due to malpractice situations of the Mexican authorities. We believe that a total reform of the social service in medicine is necessary. It is the responsibility of the authorities to cover the rural areas with permanently trained doctors without depending on recently graduated doctors. It is always important to assert our fundamental rights, including the right to protest in a peaceful manner.